Generation of Multi‐Gigahertz Trains of Phase‐Coherent Femtosecond Laser Pulses in Ti:Sapphire Waveguides. Issue 11 (19th September 2018) - Grivas, Christos; Ismaeel, Rand; Corbari, Costantino; Huang, Chung‐Che; Hewak, Dan W.; Lagoudakis, Pavlos; Brambilla, Gilberto
Abstract: Miniature lasers producing ultrashort phase‐coherent pulses at high repetition rates by stable mode‐locking in ambient conditions can offer unique capabilities in various applications, spanning from microwave photonics to telecom and biological imaging techniques. Here, the operation of graphene mode‐locked lasers based on channel waveguides written by femtosecond and picosecond laser pulses in Ti:sapphire crystals is demonstrated. Trains of pulses of 41.4 fs duration at a 21.25 GHz repetition rate are generated by capitalizing on the formation of solitons in their monolithic resonators through Gires–Tournois interferometers. The latter, allow for effective pulse shaping via tuning of the intracavity group delay dispersion while simultaneously enabling ultralow laser operating thresholds. A number of features of these sources, including their high‐brightness and broad bandwidth, are essential ingredients for achieving high longitudinal resolution and sensitivity, which are the primary performance metrics of the Fourier domain/spectral domain variant of optical coherence tomography systems. A further doubling of the laser repetition rate to 42.5 GHz is achieved by coherent pulse interleaving in optical fiber technology, thereby underlining the potential of the Ti:sapphire waveguide lasers to produce highly stable, wide‐spaced combs of phase‐coherent optical frequency lines. Abstract : Soliton‐mode‐locked Ti:sapphire channel waveguide lasers developed by ultrashort laser pulses, generate in ambient conditions and at ultralow thresholds 41.4‐fs short pulses at a 21.25‐GHz repetition rate, which is doubled to 42.5 GHz by coherent pulse interleaving in optical fiber technology. These sources of highly stable, wide‐spaced combs of phase‐coherent frequency lines are interesting for biological imaging and frequency comb spectroscopy.